High selective fluorescence imaging of cesium distribution in Arabidopsis using a bis(trihydroxyphenyl)-appended fluorescent probe with a turn-on system1. Issue 34 (15th April 2015) - Jung, Sung Ho; Hyun, Tae Kyung; Kim, Jae-Yean; Jung, Jong Hwa
<x xml:space="preserve">Abstract</x> The bis(trihydroxyphenyl)-appended ligand 1 was found to display dramatically enhanced fluorescence upon the addition of Cs+, but not with any other metal ions.